Method for preparing mullite-based porous ceramic material from biochar and coal co-gasification fly ash
Patent Information
- Application Number
- CN202510989027.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-17
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-07-17
AI Technical Summary
[0010]针对现有莫来石基多孔陶瓷制备中存在的原料单一、造孔方式依赖外加材料、孔道结构可控性差、以及工业副产物资源化利用效率低等技术瓶颈,提出一种融合工业副产物高值利用、多尺度孔道精准构建与材料功能赋能于一体的新型陶瓷制备方法
[0027]本发明引入孔道控制机制,一方面通过控制造粒时间与设备参数,并限定粒径在0.2~5 mm的区间内,不仅保证颗粒堆积的致密性,同时在陶瓷体中形成尺寸均一的规则大孔道,另一方面,烧结过程中,飞灰中残余碳组分发生原位热解并析气,形成贯通性微孔结构,有效提升陶瓷的连通孔隙率,通过该机制,构建出可人为调控的贯穿性多尺度孔道结构体系,此结构调控机制可显著提升材料的气体通透性与比表面积,为其功能应用提供结构支撑。
Smart Images

Figure CN120647423B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of porous ceramic materials technology, specifically relating to a method for preparing mullite-based porous ceramic materials using biochar and coal co-gasification fly ash as the main raw materials. It falls under the cross-technology category of industrial solid waste resource utilization and porous structure ceramic material preparation. Background Technology
[0002] Mullite (3Al₂O₃·2SiO₂) has broad application prospects in high-temperature applications such as refractory materials, thermal insulation structures, ceramic matrix composites, and functional coatings due to its excellent thermal stability, thermal shock resistance, corrosion resistance, and low coefficient of thermal expansion. In recent years, with the development of integrated structure-function material design, porous mullite ceramics have attracted increasing attention due to their simultaneous structural strength and high porosity. Its microstructural characteristics, such as porosity, pore size distribution, and connectivity, have a decisive influence on the material's functional parameters, including thermal conductivity, acoustic performance, and catalytic efficiency.
[0003] Currently, porous mullite ceramics typically use high-purity alumina and silicon sources as raw materials, and achieve pore construction through processes such as adding pore-forming agents, sacrificial templates, or foam replication. However, these methods suffer from problems such as high raw material costs, high energy consumption, and difficulty in precisely controlling the pore structure, which hinders large-scale promotion.
[0004] In contrast, the large amount of gasification fly ash generated during the co-gasification of biomass and coal, as a typical industrial byproduct, is rich in SiO2, Al2O3, and a certain amount of residual carbon and alkali metal elements (such as K and Na), possessing significant potential as a ceramic raw material. Direct disposal would not only waste resources but also pose environmental risks. Therefore, developing a process for preparing functional ceramics using gasification fly ash as the main material is currently a research hotspot in the interdisciplinary field of materials science and environmental engineering.
[0005] Currently, much research has been conducted on the preparation of mullite-based porous ceramics using industrial waste.
[0006] CN119912271A discloses a mullite porous ceramic and its preparation method. The method uses fly ash (a solid waste) as raw material, introduces andalusite as a silicon source regulator, and uses alumina or calcined bauxite as an aluminum source. The raw materials are formulated according to the near-mullite chemical composition, and the structure of the mullite ceramic is controlled by combining the raw material particle size, pressing process, and segmented sintering. In this process, near-net-shape mullite porous ceramics can be effectively prepared through particle stacking and the volume expansion accompanying mullite formation during sintering. This results in mullite-based porous ceramics with low sintering shrinkage, good gas flux, and structural strength.
[0007] CN116813367A discloses a porous ceramic and its preparation method. This method controls the source of raw materials, selecting high-alumina fly ash, mainly composed of mullite and quartz phases, as the main raw material. It rationally combines external aluminum and silicon sources and adjusts the balance between whisker generation and porosity by adding a small amount of fluorine-free whisker promoter and sintering aid, ultimately obtaining a porous ceramic with high whisker content and high porosity. In the prepared porous ceramic, the mullite whiskers have a diameter of 0.5~0.8μm, an aspect ratio of 10~30, and grow along the c-axis
[001] direction. The mullite whisker content in the product is 55~65 vol%, and the porosity of the ceramic is greater than 80%.
[0008] Although existing technologies have attempted to utilize various industrial byproducts, no research has systematically utilized biochar and coal co-gasification fly ash for the preparation of mullite porous ceramics. Furthermore, there is a lack of in-depth research and engineering implementation of the synergistic mechanism between residual carbon and alkali metal elements in fly ash. For example, the gasification behavior of residual carbon during sintering can be used to construct in-situ microporous structures, and the migratable potassium element in fly ash may impart certain catalytic activity or ionic conductivity to the material; however, there are currently few documents or technical solutions that systematically utilize these technologies.
[0009] Therefore, there is an urgent need to propose a method for preparing mullite-based porous ceramics that can systematically utilize the multi-component characteristics of co-gasified fly ash and take into account both structural regulation and functional development, so as to realize the high-value and functional transformation of industrial by-products and expand their application boundaries in filtration, thermal isolation and energy catalysis. Summary of the Invention
[0010] To address the technical bottlenecks in the existing preparation of mullite-based porous ceramics, such as the reliance on single raw materials, dependence on external materials for pore formation, poor controllability of pore structure, and low efficiency of resource utilization of industrial by-products, a novel ceramic preparation method is proposed that integrates high-value utilization of industrial by-products, precise construction of multi-scale pores, and material functional empowerment.
[0011] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0012] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash involves using biochar and coal co-gasification fly ash as silicon sources and added aluminum sources as mixed raw materials, mixing them according to a specific mass ratio of alumina and silicon oxide, adding binders and pore-forming agents, adding whisker promoters, granulating, sieving, statically pressing into blanks, drying, and sintering to obtain mullite-based porous ceramic materials.
[0013] Furthermore, the residual carbon in the biochar and coal co-gasification fly ash can act as a pore-forming agent, pyrolyzing to generate gas during sintering, thereby forming an in-situ pore structure in the ceramic matrix and enhancing the interconnected porosity of the material. The pore-forming mechanism is a dual synergistic mechanism, where the added pore-forming agent mainly constructs regular macropores, while the residual carbon in the fly ash, through thermal desorption during sintering, constructs interconnected micropores, thus achieving the integrated construction of a multi-scale, pervasive pore structure in the material.
[0014] Furthermore, the granulation conditions are as follows: an inclined high-power mixer or a disc granulator is selected, and granulation is carried out for 1 to 30 minutes. The mixing method of the binder and the mixed raw materials is step-by-step mixing or one-time mixing. During the granulation process, the granulation particle size is controlled within the range of 0.2 to 5 mm to adjust the distribution and structure of macropores in the ceramic material and to construct regular macropores.
[0015] Furthermore, the sintering specifically includes a first stage of preheating and removal, a second stage of mullite crystal phase formation and growth, and a third stage of cooling. The entire sintering process is carried out in air or an inert atmosphere.
[0016] The first stage, the preheating and removal stage, involves heating at a rate of 0.5~15℃ / min, maintaining a temperature of 400~600℃ for 1~3 hours to fully remove the pore-forming agent, binder, and volatile components.
[0017] The second stage, the mullite crystal phase formation and growth stage, involves heating at a rate of 0.5~15℃ / min, maintaining a temperature of 900~1500℃ for 1~6 hours to promote the formation of the mullite phase and crystal growth, while also promoting the precipitation of whiskers induced by the whisker promoter and the densification of the framework.
[0018] The third stage, the cooling stage, involves reducing the temperature to room temperature at a rate of 5~20℃ / min.
[0019] Furthermore, the biochar and coal co-gasification fly ash contain the following components: 8.67 wt% alumina, 50.40 wt% silicon dioxide, 4.76 wt% potassium oxide, and 25.37 wt% unburned carbon.
[0020] Furthermore, the added aluminum source is one of calcined bauxite powder, γ-Al2O3, and Al(OH)3, and its alumina content is ≥70wt%.
[0021] Furthermore, the mass ratio of alumina to silicon oxide is 1.3 to 2.3.
[0022] Furthermore, the binder is one or more of water, starch, polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose (CMC); the binder accounts for 2 to 30 wt% of the mass fraction of the mixed raw materials.
[0023] Furthermore, the pore-forming agent is one of starch, hydrogen peroxide, polymethyl methacrylate (PMMA), and ammonium bicarbonate; the pore-forming agent accounts for 5 to 40 wt% of the mass fraction of the mixed raw materials.
[0024] Furthermore, the whisker accelerator is one of B2O3, AlF3·3H2O, and MnO2; the whisker accelerator accounts for 0.2~10wt% of the mass fraction of the mixed raw materials.
[0025] Mullite-based porous ceramic materials
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] This invention introduces a pore control mechanism. On the one hand, by controlling the granulation time and equipment parameters and limiting the particle size to the range of 0.2~5 mm, not only is the compactness of particle packing guaranteed, but also a uniform and regular large pore size is formed in the ceramic body. On the other hand, during the sintering process, the residual carbon components in the fly ash undergo in-situ pyrolysis and gas evolution, forming a through-hole microporous structure, which effectively improves the interconnected porosity of the ceramic. Through this mechanism, a through-hole multi-scale pore structure system that can be artificially controlled is constructed. This structural control mechanism can significantly improve the gas permeability and specific surface area of the material, providing structural support for its functional applications.
[0028] In terms of forming, a cold isostatic pressing process is used to achieve high-density billet formation, followed by a three-stage sintering process to achieve material densification and multi-scale porous structure construction. Simultaneously, alkali metal elements in the gasified fly ash can create a sintering liquid phase, lowering the sintering temperature while promoting mullite whisker growth, demonstrating good economic efficiency and environmental friendliness. Furthermore, this invention fully utilizes the active behavior of migratory alkali metals (such as K) in fly ash at high temperatures, not only reducing the sintering temperature but also exhibiting synergistic effects in crystal phase induction, framework densification, and surface functional site formation. This endows the material with potential ion exchange capacity, weak catalytic activity, or thermoelectric response characteristics, expanding its application boundaries in high-temperature filtration, carrier catalysis, and environmental functional ceramics.
[0029] In summary, this invention provides a new approach for preparing mullite-based porous ceramics that combines structural regulation and functional development, possessing significant resource utilization value and industrialization potential. This provides technical support for promoting the high-value utilization of multi-source solid waste and the development of functional ceramics. Attached Figure Description
[0030] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0031] Figure 1 This is a SEM image of the mullite-based porous ceramic from Example 1.
[0032] Figure 2 This is an XRD image of the mullite-based porous ceramic from Example 1. Detailed Implementation
[0033] To gain a deeper understanding of this invention, we will provide a comprehensive and detailed description. However, this invention has various implementations and is not limited to the specific examples listed herein. These examples are presented to enhance a full understanding of the disclosure of this invention.
[0034] The biochar and coal co-gasification fly ash in the following examples were obtained from a fluidized bed gasifier in Shanxi Province, and contained 8.67 wt% alumina, 50.40 wt% silica, 4.76 wt% potassium oxide, and 25.37 wt% unburned carbon. The calcined bauxite powder was obtained from Inner Mongolia Autonomous Region and contained 78.45 wt% alumina.
[0035] Example 1
[0036] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash includes the following steps:
[0037] (1) The ingredients are prepared according to the mass ratio of alumina and silicon dioxide of 1.7. Then, water, starch, and B2O3 are added in a mass fraction of 10wt% of biochar, coal co-gasification fly ash and calcined bauxite powder, 10wt% of water, 3wt% of starch, and 10wt% of starch. Water acts as a binder and starch acts as both a binder and a pore-forming agent. The mixture is poured into an inclined high-power mixer for mixing and granulation. Granulation takes 5 minutes. After granulation, the mixture is passed through a 20-40 mesh standard sieve to obtain 0.425-0.850 mm granular raw materials.
[0038] (2) The obtained granular raw material is placed in a mold and formed using a tablet press at a pressure of 20 MPa. After drying, a ceramic green body is obtained.
[0039] (3) The ceramic green body is placed in an electric heating furnace for firing. First, the temperature is raised to 500℃ at a rate of 2℃ / min and held for 1 hour. Then, the temperature is raised to 1350℃ at a rate of 10℃ / min and held for 3 hours to promote the formation of mullite phase and crystal growth, while promoting the precipitation of whiskers induced by whisker promoter and the densification of the skeleton. Finally, the temperature is lowered to room temperature at a rate of 15℃ / min and cooled with the furnace to obtain mullite-based porous ceramic material.
[0040] To further verify the structure and properties of the prepared mullite-based porous ceramic material, several structural characterization and performance tests were performed on the sample obtained in Example 1, as detailed below:
[0041] The sample was examined using a scanning electron microscope (SEM) as follows: Figure 1 As shown in the figure, the analysis reveals that its cross-section exhibits a distinct multi-scale pore structure, comprising uniformly distributed regular macropores (approximately 1–2 mm in diameter) and interconnected micropores (approximately 0.5–10 μm in diameter). The macropores mainly originate from the decomposition of the added starch pore-forming agent, while the micropores are caused by the in-situ thermal desorption of residual carbon components from fly ash during sintering. The pore structure exhibits good connectivity.
[0042] Specific surface area analysis was performed using the nitrogen adsorption method (BET), and the results showed that the specific surface area of the material was 16.8 m². 2 The material has a porosity of 48.3% and an average pore size of 7.6 nm, which conforms to the structural characteristics of typical porous ceramics.
[0043] Gas permeability was tested using the constant flow differential pressure method (air medium, 25℃ ambient temperature). At a pressure difference of 1.0 kPa, the gas flux reached 1150 mL / min·cm. 2 This indicates that the material has good gas permeability and is suitable for functional applications such as high-temperature filtration and gas reaction medium transport.
[0044] XRD diffraction results are as follows Figure 2 As shown, the results indicate that the main crystalline phases in the material are mullite (3Al2O3·2SiO2), potassium feldspar (K2O·Al2O3·6SiO2), and calcium feldspar (CaO·Al2O3·2SiO2), with no obvious impurities and a complete crystal structure. Combined with the rod-shaped whisker morphology observed by SEM, it can be inferred that the B2O3 whisker induction effect is significant, which helps to enhance the structural stability of the ceramic matrix.
[0045] In summary, the prepared mullite-based porous ceramics not only possess good structural controllability and compact molding properties, but also exhibit high specific surface area and gas permeability, laying a structural foundation for subsequent applications in high-temperature gas filtration, catalytic reaction carriers, thermal insulation, or electrical performance.
[0046] Example 2
[0047] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash includes the following steps:
[0048] (1) The ingredients are prepared according to the mass ratio of alumina and silicon dioxide of 2:1. Then, 10 wt% polyvinyl alcohol (PVA), 10 wt% polymethyl methacrylate (PMMA), and 5 wt% MnO2 are added, accounting for the mass fraction of biochar, coal co-gasification fly ash and γ-Al2O3 powder. In this case, polyvinyl alcohol (PVA) acts as a binder and polymethyl methacrylate (PMMA) acts as a pore-forming agent. The mixture is poured into a disc granulator for mixing and granulation. Granulation is carried out for 5 min. After granulation, the mixture is passed through a 20-40 mesh standard sieve to obtain 0.425-0.850 mm granular raw material.
[0049] (2) The obtained granular raw material is placed in a mold and formed using a tablet press at a pressure of 20 MPa. After drying, a ceramic green body is obtained.
[0050] (3) The ceramic green body is placed in an electric heating furnace for firing. First, the temperature is raised to 500℃ at a rate of 2℃ / min and held for 1 hour. Then, the temperature is raised to 1420℃ at a rate of 10℃ / min and held for 3 hours to promote the formation of mullite phase and crystal growth. At the same time, the whisker precipitation induced by the whisker promoter and the densification of the skeleton are promoted. Finally, the temperature is lowered to room temperature at a rate of 15℃ / min. After cooling in the furnace, mullite-based porous ceramic material is obtained.
[0051] Gas permeability test results: The gas flux of the mullite-based porous ceramic obtained in Example 2 was tested using the constant flow differential pressure method (air medium, room temperature 25℃). At a pressure difference of 1.0 kPa, the gas flux of the test sample was 860 mL / min·cm. 2 Slightly lower than 1150 mL / min·cm in Example 1 2 This difference may be related to the presence of a small amount of corundum phase in the material. Corundum has high density and crystal integrity, which may partially inhibit the formation of through-holes during sintering, thereby reducing gas permeability.
[0052] Compared to Example 1, this embodiment uses γ-Al₂O₃ powder and an alumina to silicon oxide mass ratio of 2:1, which increases the aluminum-silicon ratio in the reaction system. This also raises the sintering temperature, leading to excessive energy consumption and the formation of the corundum phase. Replacing starch with polyvinyl alcohol (PVA) and polymethyl methacrylate (PMMA) as binders and pore-forming agents makes the process more complex.
[0053] Example 3
[0054] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash includes the following steps:
[0055] (1) The ingredients are prepared according to the mass ratio of alumina and silicon dioxide of 1.5, and then sodium carboxymethyl cellulose (CMC) of 10 wt% of the total mass of biochar, coal co-gasification fly ash and calcined bauxite powder, 10 wt% of hydrogen peroxide, and 2 wt% of AlF3·3H2O are added. CMC is used as a binder and hydrogen peroxide is used as a pore-forming agent. The mixture is poured into a disc granulator, mixed evenly and granulated. The granulation time is 15 min and the sieve particle size is 0.425~0.850 mm.
[0056] (2) The obtained granular raw material is placed in a mold, formed by a tablet press at a pressure of 25 MPa, and dried to obtain a ceramic green body;
[0057] (3) The ceramic green body is placed in an electric furnace for sintering. The heating rate is 5℃ / min. First, it is heated to 550℃ and held for 1h. Then, it is heated to 1300℃ and held for 2h. Finally, it is cooled to room temperature at 10℃ / min to obtain mullite-based porous ceramic material.
[0058] The obtained ceramic material has a specific surface area of 24.6 m² / g, a porosity of 52.7%, and an average pore size of 11.4 nm, exhibiting good micro-to-mesoporous structure and gas transport capability.
[0059] Example 4
[0060] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash includes the following steps:
[0061] (1) The alumina and silicon oxide were mixed in a mass ratio of 1.3, and 10wt% water and 10wt% ammonium bicarbonate were added as binders and pore-forming agents. 5wt% MnO2 was added as a whisker promoter. The mixture was put into an inclined high-power mixer for mixing and granulation. The granulation time was controlled at 10min. The resulting particle size range was controlled at 0.2~0.6 mm.
[0062] (2) The granular raw material is loaded into the mold and pressed into shape under a pressure of 20 MPa. After drying, a ceramic green body is obtained.
[0063] (3) The green body is sintered in air atmosphere. The procedure is as follows: heat up to 500℃ (2℃ / min) and hold for 1h, then heat up to 1250℃ (8℃ / min) and hold for 4h, and cool down at a rate of 10℃ / min to room temperature.
[0064] The obtained ceramic material has a specific surface area of 31.2 m² / g, a porosity of 65.4%, an average pore size of 42.8 nm, a uniform structure, and good gas flux.
[0065] Example 5
[0066] A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash includes the following steps:
[0067] (1) Alumina and silicon dioxide were mixed in a mass ratio of 2.2, and 10wt% polyvinyl alcohol (PVA), 15wt% PMMA and 0.5wt% B2O3 were added as binders, pore-forming agents and whisker promoters. After mixing, the mixture was put into an inclined high-power mixer for granulation for 20 min. The particle size was controlled to be 0.85~1.2 mm after sieving.
[0068] (2) The obtained granules are formed in a pressing mold at a pressure of 30 MPa and dried into ceramic green bodies;
[0069] (3) The sintering process is as follows: heat up to 600℃ (3℃ / min) and hold for 2 hours, then heat up to 1450℃ (12℃ / min) and hold for 3 hours, and finally cool down to room temperature at 15℃ / min.
[0070] The obtained ceramic material has a specific surface area of 13.4 m² / g, a porosity of 39.6%, and an average pore size of 712 nm. The pore structure contains a significant number of macropores, making it suitable for high-temperature particle filtration and carrier reaction.
[0071] Contents not described in detail in this specification are prior art known to those skilled in the art. Although illustrative specific embodiments of the invention have been described above to facilitate understanding by those skilled in the art, it should be understood that the invention is not limited to the scope of the specific embodiments. Various modifications are readily apparent to those skilled in the art as long as they fall within the spirit and scope of the invention as defined and determined by the appended claims, and all inventions utilizing the concept of this invention are protected.
Claims
1. A method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash, characterized in that: Using biochar and coal co-gasification fly ash as silicon source and added aluminum source as mixed raw materials, the raw materials are batched at a mass ratio of alumina to silicon oxide of 1.3~2.
3. Binders and pore-forming agents are added, whisker promoters are added, and after granulation, sieving, static pressing into blanks, drying and sintering, mullite-based porous ceramic materials are obtained. The biochar and coal co-gasification fly ash contains the following components: alumina 8.67 wt%, silicon dioxide 50.40 wt%, potassium oxide 4.76 wt%, and unburned carbon 25.37 wt%. The granulation conditions are as follows: an inclined high-power mixer or a disc granulator is used, and granulation takes 1 to 30 minutes. The binder and the mixed raw materials are mixed in a stepwise or one-time manner. During the granulation process, the particle size is controlled within the range of 0.2 to 5 mm to adjust the distribution and structure of macropores in the ceramic material and to construct regular macropores. The binder accounts for 2-30 wt% of the mass fraction of the mixed raw materials; the pore-forming agent accounts for 5-40 wt% of the mass fraction of the mixed raw materials. The residual carbon in the fly ash pyrolyzes to generate gas during sintering, forming an in-situ pore structure in the ceramic matrix, which together with the added pore-forming agent constitutes a dual synergistic pore-forming mechanism.
2. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The sintering process specifically includes a first stage of preheating and removal, a second stage of mullite crystal phase formation and growth, and a third stage of cooling. The entire sintering process is carried out in air or an inert atmosphere. The first stage, the preheating and removal stage, involves heating at a rate of 0.5~15℃ / min, maintaining a temperature of 400~600℃ for 1~3 hours to fully remove the pore-forming agent, binder, and volatile components. The second stage, the mullite crystal phase formation and growth stage, involves heating at a rate of 0.5~15℃ / min, maintaining a temperature of 900~1500℃ for 1~6 hours to promote the formation of the mullite phase and crystal growth, while also promoting the precipitation of whiskers induced by the whisker promoter and the densification of the framework. The third stage, the cooling stage, involves reducing the temperature to room temperature at a rate of 5~20℃ / min.
3. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The external aluminum source is one of calcined bauxite powder, γ-Al2O3, and Al(OH)3, and its alumina content is ≥70wt%.
4. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The mass ratio of alumina to silicon oxide is 1.3 to 2.
3.
5. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The binder is one or more of water, starch, polyvinyl alcohol (PVA), and sodium carboxymethyl cellulose.
6. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The pore-forming agent is one of starch, hydrogen peroxide, polymethyl methacrylate (PMMA), and ammonium bicarbonate.
7. The method for preparing mullite-based porous ceramic materials from biochar and coal co-gasification fly ash according to claim 1, characterized in that: The whisker accelerator is one of B2O3, AlF3·3H2O, and MnO2; the whisker accelerator accounts for 0.2~10wt% of the mass fraction of the mixed raw materials.
8. The mullite-based porous ceramic material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The material has a specific surface area of 10~50 m² / g, a porosity of 35~85%, and an average pore size of 5~1000 nm.
Citation Information
Patent Citations
Mullite porous ceramic and preparation method thereof
CN119912271A
Porous ceramic and preparation method thereof
CN116813367A